EFFECT OF MODERATE RUNNING ON SPORTS INJURY REHABILITATION - Zhang,Xuelei (2022)
ABSTRACT Introduction Running has become one of the most popular sports and fitness methods for low cost, convenience, and easy adherence. This has made the characteristics and rules of running-related sports injuries a key research issue in sports medicine and public health. Objective Evaluate the effects of moderate running on sports injuries rehabilitation. Methods This paper uses mathematical statistics to study some groups that have been running for a long time (n=369). The causes of sports injuries analyses and risks are performed by questionnaire. Results Relaxation after exercise is a protective factor for sports injuries. The time of maintenance of the running habit and the previous sport’s history are factors influencing the risk for a sport’s injury. Conclusion Amateur runners have a high rate of running injuries. The knee is the area with the highest injury incidence. Weight-loss running increases the risk of injury. An individually moderate running training plan can reduce the risk of running injuries. Evidence level II; Therapeutic Studies - Investigating the results.